STRATEGI PEMASARAN FIBRE DI PT. POLYSINDO EKA PERKASA KARAWANG MARKETING STRATEGY AT PT. POLYSINDO EKA PERKASA KARAWANG - NADEAK, BANUARA (Jurnal Politikom Indonesiana, 2017)
ABSTRACT In leading the market PT. Polysindo Eka Perkasa always ensuring quality, competitive prices, excellent service and reliability. This can be shown by production results in 1996 amounted to 137,956,343.6 kg and compared with 2001 amounted to 140,964,592.1 kg.Knives analysis results by SWOT, use Internal Factors Analysis Summary (IFAS), that the total value of strength factor 1,90 and a total value of weakness 1,70. With the basis this analysis, the value of IFAS matrix 0,20. While Eksternal Factors Analysis Summary (EFAS) shown the total value of opportunity factor 1,65 and threat factor 2,10. So by analysis the value of EFAS matrix -0,45 therefore by SWOT analysis diagram at quadrant 2 using by diservikasi strategy with develop quality and competitive price competition with the long-term and do corporate (MOU) with the long-term by transport fleet in order to distribute on time. The results of the distribution made fiber production safety triangle with associated components is the Marketing Manager, Production Planning and Control Components Control Quality of the distribution of the goods on target. Key words : Marketing Strategy, Quality Control, Standar Value of Sales